Critical-Thinking Instrument Based on Google Form: Development on Work and Energy Materials. (February 2020) - Yana, Evi; Irwandani,; Sari, Nopita; Amirrudin,; Amrullah, Afif; Jatmiko, Agus
Abstract: Curriculum 2013 requires students to have critical-thinking skills, especially in physics. Preliminary research conducted at several schools found the lack of questioning instruments that require students to have critical-thinking skills and teachers in conducting evaluations still using conventional paper media (paper tests). The purpose of this research is to find out how the characteristics of the instrument about the ability to think critically using Google Form and to find out how the validity and reliability of the items as well as the responses of teachers and students to the instrument about the critical-thinking skills using Google Form. The instrument developed was a multiple-choice grid test that was oriented towards students' critical-thinking skills. The assessment instruments that have been developed in this study are declared valid and reliable as well as the response of teachers and students very well to the question instruments developed.